Why Green-Minded Employees are Key to Sustainability in Business and Nature - Febby Chika Putri Mulfag (International Journal Of Economics Social And Technology, 2026)
This study systematically reviews the role of Green Human Capital in strengthening business and environmental sustainability. Using a Systematic Literature Review approach guided by the PRISMA procedure, this study analyzed articles obtained from Scopus, Web of Science, ScienceDirect, Emerald Insight, and Google Scholar published between 2008 and 2024. From the identification and screening process, 16 eligible articles were included in the final synthesis. The findings reveal four major themes: the antecedents of Green Human Capital, including green training, green HRM, environmental awareness, and personality traits; the mechanisms through which Green Human Capital supports sustainability, particularly green innovation and pro-environmental behavior; the outcomes of Green Human Capital, including environmental quality, business performance, and competitive advantage; and contextual factors such as sector, policy environment, and time horizon. The study contributes to the literature by positioning Green Human Capital as a strategic sustainability capability that connects Human Capital Theory, Resource-Based View, AMO Theory, and Triple Bottom Line perspectives. Practically, the findings suggest that organizations should invest in environmentally knowledgeable and skilled employees to enhance innovation, competitiveness, and long-term sustainability performance.